The Depiction of Desertion in Charles Frazier's Cold Mountain - Moucha, Josef (Univerzita Pardubice, 2025)
This bachelor thesis focuses on the depiction of desertion and its impact on characters in the novel Cold Mountain by Charles Frazier. The theoretical part of this paper attempts to define the term desertion within the context of the American Civil War, analyzing its causes and perceptions within the Confederacy. The analytical part delves into the individual experiences of key characters, contrasting their motivations and perceptions of desertion with the established historical context.
Vyobrazení sběhnutí v díle „Cold Mountain“ od Charlese Fraziera
Keywords: desertion; deserters; American Civil War; history; Confederacy; soldiers; citizens; characters; Frazier, Charles; Cold Mountain; sběhnutí; sběhové; americká Občanská válka; Konfederace; vojáci; občané; postavy